2013
DOI: 10.1371/journal.pone.0059942
|View full text |Cite
|
Sign up to set email alerts
|

Gender Affects Skin Wound Healing in Plasminogen Deficient Mice

Abstract: The fibrinolytic activity of plasmin plays a fundamental role in resolution of blood clots and clearance of extravascular deposited fibrin in damaged tissues. These vital functions of plasmin are exploited by malignant cells to accelerate tumor growth and facilitate metastases. Mice lacking functional plasmin thus display decreased tumor growth in a variety of cancer models. Interestingly, this role of plasmin has, in regard to skin cancer, been shown to be restricted to male mice. It remains to be clarified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Androgens were shown to have a proinflammatory effect on wounds, impairing re-epithelialization, whereas oestrogens had an anti-inflammatory effect, with males and females responding differently with regard to stress [ 13 ]. A study on plasminogen-deficient mice demonstrated marked gender effects on wound healing [ 14 ]. Loss of plasmin-dependent fibrinolysis leads to abnormal wound healing and development of pseudomembranes.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens were shown to have a proinflammatory effect on wounds, impairing re-epithelialization, whereas oestrogens had an anti-inflammatory effect, with males and females responding differently with regard to stress [ 13 ]. A study on plasminogen-deficient mice demonstrated marked gender effects on wound healing [ 14 ]. Loss of plasmin-dependent fibrinolysis leads to abnormal wound healing and development of pseudomembranes.…”
Section: Discussionmentioning
confidence: 99%
“…23 Plasmin is a serine protease that exhibits trypsin-like broad specificity, particularly when plasminogen is activated by urokinase plasminogen activator (uPA) in a cell surface receptormediated process. 24,25 Plasmin generated at the cell surface plays a critical role in degradation of extracellular matrix (ECM) resulting in modulation of several processes including tissue remodeling, 26,27 cell invasion and metastasis, 28,29 chemotaxis, 29,30 wound healing and tissue repair, [31][32][33] neuritogenesis, 34,35 ovulation and embryo implantation, 36,37 and others. 38 Plasmin itself can degrade components in the ECM such as laminin, 39 fibronectin, 40 and collagens.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether this apparent advantage present in females also involves the wound healing process. In particular, the dorsal incisional wound healing process—generated in a similar experimental setting in this manuscript—showed no difference between C57BL/6 male and female mice after 50 days post-injury [ 2 ]. In this last report, female mice tended to have more rapid wound healing, especially in the time-lapse of up to 20 days.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence describes contrasting influences of androgenic and estrogenic sex steroids on the healing of acute skin wounds, in which the former inhibits whereas the latter accelerates recovery [ 1 ]. However, gender differences in wound repair parameters would not intuitively be expected [ 2 , 3 ]. Since healing is a complex mechanism involving several processes, such as inflammation, coagulation, and angiogenesis, among others, it is feasible that female mice may have certain advantages in some of those processes.…”
Section: Introductionmentioning
confidence: 99%